Modal Sosial, Kinerja Petahana, dan Menurunnya Signifikansi Politik Identitas: Bukti dari Pilkada Belitung Timur 2024 - Ranto Ranto (Society, 2025)
This study examines the declining salience of identity politics in local electoral competition by analyzing the victory of an ethnic Chinese candidate in the 2024 East Belitung regional election. Drawing on a quantitative survey of 400 respondents, the research investigates how ethnic identity, social capital, and incumbent performance interact in shaping voter behavior within a multi-ethnic and predominantly Muslim society. Contrary to dominant explanations that emphasize ethnic identity as the primary determinant of electoral outcomes, the findings demonstrate that strong social capital—reflected in high levels of interethnic trust and tolerance—combined with negative evaluations of incumbent performance significantly weakened the role of ethnic sentiment in voting decisions. The study shows that voters were more inclined to prioritize governance performance, inclusiveness, and perceived responsiveness over shared ethnic or religious identity. By integrating perspectives from political representation, voting behavior, and social capital theory, this research argues that robust social trust and poor incumbent performance can function as critical mechanisms that reduce the mobilizing power of identity politics in local democracy. The East Belitung case provides empirical evidence that minority candidates can successfully overcome primordial barriers when institutional performance and social cohesion outweigh identity-based appeals.